THE ROLE OF MULTI-MEDIA APPROACH INI NARROWING THE KAP-GAPS AMONG THE FARMERS OF THE STRATEGIC EXTENSION CAMPAIGN IN MUDA IRRIGATION SCHEME - Ageng Setawan Herianto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2000)
The purpose of the study was to determine whether the multi-media approach in the brown plant hopper (BPH) control management Strategic Extension Campaign (SEC) has narrowed the knowledge, attitude, and practice (KAP)-gaps among the farmers with low and high socio-economic status (SES) in the MADA area, Malaysia. The research was designed as the before and after campaign study.The KAP-survey results as the secondary data of the study, was the benchmark data of the before campaign study. Data of the after campaign study were gathered by means of personal interview with 189 farmers using the structured questionnaire.Findings reveal that KAP-level of both farmers with low and high-SES farmers on the technology of BPH control management had increased after the multi-media campaign. However, the multi-media approach of SEC had narrowed the KAP-gaps of these farmers. Therefore, the study found that the multi-media approach of the SEC is the appropriate approach in narrowing the KAP-gaps among the farmers.